Radiation induces ESCRT pathway dependent CD44v3+ extracellular vesicle production stimulating pro-tumor fibroblast activity in breast cancer - Clark, Gene Chatman; Hampton, James David; Koblinski, Jennifer E.; Quinn, Bridget; Mahmoodi, Sitara; Metcalf, Olga; Guo, Chunqing; Peterson, Erica; Fisher, Paul B.; Farrell, Nicholas P.; Wang, Xiang-Yang; Mikkelsen, Ross B. (Frontiers in Oncology, 2022)
Despite recent advances in radiotherapeutic strategies, acquired resistance remains a major obstacle, leading to tumor recurrence for many patients. Once thought to be a strictly cancer cell intrinsic property, it is becoming increasingly clear that treatment-resistance is driven in part by complex interactions between cancer cells and non-transformed cells of the tumor microenvironment. Herein, we report that radiotherapy induces the production of extracellular vesicles by breast cancer cells capable of stimulating tumor-supporting fibroblast activity, facilitating tumor survival and promoting cancer stem-like cell expansion. This pro-tumor activity was associated with fibroblast production of the paracrine signaling factor IL-6 and was dependent on the expression of the heparan sulfate proteoglycan CD44v3 on the vesicle surface. Enzymatic removal or pharmaceutical inhibition of its heparan sulfate side chains disrupted this tumor-fibroblast crosstalk. Additionally, we show that the radiation-induced production of CD44v3+ vesicles is effectively silenced by blocking the ESCRT pathway using a soluble pharmacological inhibitor of MDA-9/Syntenin/SDCBP PDZ1 domain activity, PDZ1i. This population of vesicles was also detected in the sera of human patients undergoing radiotherapy, therefore representing a potential biomarker for radiation therapy and providing an opportunity for clinical intervention to improve treatment outcomes.